(Invited) Understanding Downstream Risk from Lithium-Ion Battery Thermal Runaway & Designing for Safety. (8th April 2019) - Spray, Ryan; Barry, Michael; Vickery, James
Abstract : With continued advances in battery technologies, batteries have become one of the leading solutions for not only portable power applications but also energy storage applications. Because of the high energy density in advanced batteries, one key safety goal is preventing the unintended release of stored energy. A catastrophic failure of a battery pack can occur if one or more cells in the battery pack undergo a thermal runaway event that results in a rapid release of the stored energy in the battery. Thermal runaway can lead to a release of flammable gases and heat, which can potentially result in fire and explosions. The design of effective thermal management systems or fire mitigation systems requires proper quantification of the thermal failure characteristics. This presentation will detail several research activities that have been developed to analyze and quantify thermal safety aspects of batteries, as well as to identify/quantify potential toxicology hazards. This process involves real-time gas analysis from lithium-ion battery failure events, as well as post-failure composition analysis and identification of gas combustion properties. The implications of this work toward designing for safety and integration into risk analyses will be discussed.